Control culture : Foucault and Deleuze after discipline - Beckman, Frida (Edinburgh University Press, 2018)
Starting from Deleuze's brief but influential work on control, the 11 essays in this book questions how contemporary control mechanisms influence, and are influenced by, cultural expression. They also collectively revaluate Foucault and Deleuze's theories of discipline and control in light of the continued development of biopolitics